Reduced Germination of Orobanche cumana Seeds in the Presence of Arbuscular Mycorrhizal Fungi or Their Exudates - Louarn, Johann; Carbonne, Francis; Delavault, Philippe; Bécard, Guillaume; Rochange, Soizic (PLOS ONE, 2012)
Broomrapes (Orobanche and Phelipanche spp) are parasitic plants responsible for important crop losses, and efficient procedures to control these pests are scarce. Biological control is one of the possible strategies to tackle these pests. Arbuscular Mycorrhizal (AM) fungi are widespread soil microorganisms that live symbiotically with the roots of most plant species, and they have already been tested on sorghum for their ability to reduce infestation by witchweeds, another kind of parasitic plants. In this work AM fungi were evaluated as potential biocontrol agents against Orobanche cumana, a broomrape species that specifically attacks sunflower. When inoculated simultaneously with O. cumana seeds, AM fungi could offer a moderate level of protection against the broomrape. Interestingly, this protection did not only rely on a reduced production of parasitic seed germination stimulants, as was proposed in previous studies. Rather, mycorrhizal root exudates had a negative impact on the germination of O. cumana induced by germination stimulants. A similar effect could be obtained with AM spore exudates, establishing the fungal origin of at least part of the active compounds. Together, our results demonstrate that AM fungi themselves can lead to a reduced rate of parasitic seed germination, in addition to possible effects mediated by the mycorrhizal plant. Combined with the other benefits of AM symbiosis, these effects make AM fungi an attractive option for biological control of O. cumana.